Revitalisasi Bangunan Kuno; Menggali Potensi Seni dan arsitektur Dalam Pelestarian Museum Dr. Saleh di Probolinggo, Jawa Timur - Maslahatul Ummah; Fatimah Mahadivinta Rahmaillah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The revitalization of ancient buildings has an important role in preserving cultural heritage and also in developing the potential of art and architecture in Indonesia. In this research, the case study in this context will be the Dr. Saleh is in the city of Probolinggo, East Java. This museum was built in the 20th century and has high historical and architectural value. This research uses a qualitative approach in order to analyze the aesthetic, historical and social aspects of the building. By showing research results that the revitalization of museums can optimize their function as public spaces, increase the preservation of cultural heritage, and attract the interest of tourists. Through several art and educational programs, the Dr. Saleh was able to transform into a center of creativity that connects past and present generations. From the results of this analysis, it is recommended that revitalization be carried out while maintaining the original elements of the building, while adding several modern facilities that can support interaction with visitors. With this approach, the museum not only functions as a collection storage center but can also be used as an education and arts center that contributes to the development of local communities as well as tourism. It is also hoped that this research will be able to provide guidance for the revitalization of other historical buildings in Indonesia.